In-vitro Differentiation of Human Umbilical Cord Wharton's Jelly Mesenchymal Stem Cells to Insulin-Producing Cells - Masoomeh Nekohi Madoei; Negar Azarpira; Ladan Sadeghi; Solmaz Kamali Far (Fasa University of Medical Sciences, 2015)
Background & Objective: Diabetes is a major chronic metabolic disease in the world. Islet transplantation is a way to treat diabetes. Unfortunately, this method is restricted due to graft rejection and lack of donor islets. Mesenchymal Stem Cells (MSCS) have the ability to differentiate into Insulin-Producing Cells (IPCs). In this study, Human Umbilical Mesenchymal Stem Cells (HUMSCS) were induced to differentiate into pancreatic β-like cells.   Materials & Methods: The samples were collected after cesarean section delivery at Hafez hospital. HUMSCS were cultured in sterile condition, in three steps for 20 days in DMEM-F12, Retinoic Acid (RA), Epidermal Growth Factor (EGF), exendin-4, Fetal Bovine Serum (FBS), and antibiotic. Then, they were differentiated into IPC. DTZ staining employed for determining the presence of insulin and Reveres Transcription- Polymerase Chain Reaction (RT-PCR) was done for identifying of gene expression including insulin, PDX1, and NGN3. The Insulin concentration was also evaluated by Immunoradiometric assay.   Results: HUMSCS gradually changed from fibroblast-shaped cells to epithelial-like cells and eventually to IPC under special conditions. RT-PCR experiments revealed that these cells expressed insulin, PDX1, and NGN3 genes. The cells became red color when stained with DTZ and the insulin secretion was confirmed.   Conclusion: HUMSCS have the ability to differentiate into islet-like cells in vitro and may be a new potential source for cell transplantation in diabetes treatment.